2007
DOI: 10.1529/biophysj.106.097618
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Conserved Glycine in the SH1-SH2 Helix Affects the Load-Dependent Kinetics of Myosin

Abstract: The ATP hydrolysis rate and shortening velocity of muscle are load-dependent. At the molecular level, myosin generates force and motion by coupling ATP hydrolysis to lever arm rotation. When a laser trap was used to apply load to single heads of expressed smooth muscle myosin (S1), the ADP release kinetics accelerated with an assistive load and slowed with a resistive load; however, ATP binding was mostly unaffected. To investigate how load is communicated within the motor, a glycine located at the putative fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 42 publications
7
60
0
Order By: Relevance
“…This finding has important implications for myosin force production and ATP utilization as sarcomere length changes throughout a contraction. Slower MgADP release at longer sarcomere length also provides supporting evidence for a strain-dependent MgADP release mechanism in slow-twitch skeletal fibers, consistent with single-molecule optical trap measurements describing this mechanism in multiple muscle myosin isoforms (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding has important implications for myosin force production and ATP utilization as sarcomere length changes throughout a contraction. Slower MgADP release at longer sarcomere length also provides supporting evidence for a strain-dependent MgADP release mechanism in slow-twitch skeletal fibers, consistent with single-molecule optical trap measurements describing this mechanism in multiple muscle myosin isoforms (31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 78%
“…Thus, it is likely that these structural alterations to the myofilaments also influence load-dependent mechanisms of MgADP release to slow cross-bridge detachment. Further studies have suggested that release of MgADP requires additional movement of the myosin head after the power stroke to induce a conformational change in the nucleotide binding pocket, freeing MgADP (31)(32)(33)(34)36,62). This ''double step'' was observed in both slow and fast skeletal myosins, and was associated with MgADP release from myosin, in single-molecule optical trap experiments (31).…”
Section: Discussionmentioning
confidence: 98%
“…To reduce the stiffness of the laser traps, a partial force clamp was used (27). In brief, a 20-kHz closed loop feedback system was applied by linking the bead and laser trap positions via acoustic optical deflectors (28). The feedback frequency response is in excess of the corner frequency obtained from the Lorentzian form power spectrum of the trapped bead displacement in solution (Ͻ500 Hz (29)).…”
Section: Methodsmentioning
confidence: 99%
“…Because ADP release is rate limiting for unloaded shortening velocity (17) and is thought to be a strain-dependent state in the actomyosin biochemical cycle (18)(19)(20)(21), the ADP-induced inhibition of velocity was measured in the presence and absence of load imposed by α-actinin (Fig. 3).…”
Section: Rlc Depletion Andmentioning
confidence: 99%